Characterising labour market self-containment in London with geographically arranged small multiples. (September 2019) - Beecham, Roger; Slingsby, Aidan
Abstract: We present a collection of small multiple graphics that support analysis and understanding of the geography of labour-market self-containment across London's 33 boroughs. Ratios describing supply-side self-containment, the extent to which working residents access jobs locally, and demand-side self-containment, the extent to which local jobs are filled by local resident workers, are first calculated for professional and non-professional occupations and encoded directly through geographically-arranged bar charts. The full distribution of workers into-and out-of- boroughs that underpins these ratios is then revealed via Origin-Destination flows maps (OD maps) – sets of geographically-arranged choropleths. In order to make relative and absolute comparison of borough-to-borough frequencies between occupation types, these OD maps are coloured according to signed chi-square residuals: for every borough-to-borough pair, we compare the observed number of flows to access professional versus non-professional jobs against the number that would be expected given the distribution of those jobs across London boroughs. Our geographically-arranged small multiples demonstrate potential for spatial analysis: a rich, multivariate structure is depicted that reflects London's economic geography and that would be difficult to expose using non-visual means.